2019
DOI: 10.3390/info11010012
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Cultural Heritage Image Classification: Comparison Based on Attribute Selection

Abstract: Image classification is one of the most important tasks in the digital era. In terms of cultural heritage, it is important to develop classification methods that obtain good accuracy, but also are less computationally intensive, as image classification usually uses very large sets of data. This study aims to train and test four classification algorithms: (i) the multilayer perceptron, (ii) averaged one dependence estimators, (iii) forest by penalizing attributes, and (iv) the k-nearest neighbor rough sets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…Two types of convolutional neural networks were applied, AlexNet and Inception V3, as well as two residual networks, ResNet and Inception-ResNet-v2. The dataset included more than 10,000 images, and the obtained results revealed that deep learning methods achieved better accuracy when dealing with complex problems such as image classification, compared to other cutting-edge techniques [37].…”
Section: Applications In Cultural Heritagementioning
confidence: 99%
See 1 more Smart Citation
“…Two types of convolutional neural networks were applied, AlexNet and Inception V3, as well as two residual networks, ResNet and Inception-ResNet-v2. The dataset included more than 10,000 images, and the obtained results revealed that deep learning methods achieved better accuracy when dealing with complex problems such as image classification, compared to other cutting-edge techniques [37].…”
Section: Applications In Cultural Heritagementioning
confidence: 99%
“…The results revealed that, in terms of accuracy, RNN achieved the highest performance, classifying 92% of the text data accurately. In terms of CNN, the best accuracy was achieved for image and video classification (76% each), while audio classification obtained only 57% accuracy [37].…”
Section: Applications In Cultural Heritagementioning
confidence: 99%
“…Several studies have developed cultural heritage documentation and implemented different methods to classify cultural heritage [13]. For example, in the study of architectural heritage, the authors proposed the image dataset of more than 10.000 images classified into ten classes, i.e., different architectural heritage types such as columns, domes, gargoyles, and vault [14].…”
Section: Related Workmentioning
confidence: 99%
“…Sınıflandırma, sette en yakın komşuları bulmak ve karar için oy vermek suretiyle yapılır. RSeslibKnn, görüntü sınıflandırmasında kullanılan son teknoloji tekniklerin bir temsili, ek olarak geliştirilen kNN modelidir [14].…”
Section: Rseslibknnunclassified